The end of tax incentives in mining? Tax policy and mining foreign direct investment in Africa - (:unkn) unknown (My University, 2021)
African countries generally cut corporate income tax (CIT) rates in the hopes of attracting foreign direct investment (FDI), but the effectiveness of tax rate reductions in attracting extractive industries FDI is controversial. This paper estimates the impact of CIT rates, as applied to mining companies, on FDI inflows to the gold and silver sectors of African economies. The estimation results indicate that the impact of the mining CIT rate on the host country’s gold and silver FDI inflows is negative, but not statistically significant, at the conventional levels of significance. These results indicate that cuts in CIT rates applied to mining companies will not necessarily attract FDI to gold and silver projects. Moreover, we find a strategic complementarity in gold and silver FDI inflows between countries, suggesting that an increase in the host country’s gold and silver FDI inflows may stimulate FDI to gold and silver projects in neighbouring countries. Furthermore, the results show that infrastructure, government stability and gold and silver reserves positively affect gold and silver FDI inflows. The main findings of the paper suggest that, instead of granting corporate tax incentives, governments may consider improving the quality of socio-economic infrastructure, the availability of geological information, and promoting political and economic stability for attracting mining investments.
Keywords: African Research